Outline of a nuclear seawater desalination plant for the Shandong Peninsula. (1st January 2004) - Wenxiang, Zheng; Yajun, Zhang
A pre-project study of the Shandong nuclear seawater desalination plant was carried out in 2001. The plant will produce 160, 000 m³/d of potable water using a 200 MWth nuclear heating reactor, developed by INET, coupled to a high-temperature multi-effect distillation process. This paper presents an outline of the Shandong desalination project, including the main features of the reactor and desalination plants, interface considerations between the reactor and desalination plants and some economic data.